Rappresentanza e governo alla svolta del nuovo secolo - Sandro, Rogari (Firenze University Press, 2006)
The book presents the proceedings of the conference held in the Aula Magna of the University of Florence on 28 and 29 October 2004. The objective of the conference was to study, through a multidisciplinary approach, the question of government and representation at local, national and European level. Among the central issues addressed during the meeting were models of representation, the links between representation and civil society and the functions of the representative organs.